PATH-31. METHYLATION SUBCLASS RECEPTOR TYROSINE KINASE II AS A DRIVER FOR SEIZURES IN IDH-WILDTYPE GLIOBLASTOMA. (12th November 2021) - Drexler, Richard; Eckhardt, Alicia; Westphal, Manfred; Schüller, Ulrich; Dührsen, Lasse; Ricklefs, Franz
Abstract: BACKGROUND: Seizures are a common symptom of patients suffering from glioblastoma and there is evidence that these tumours are morphologically different. However, the relationship of DNA methylation and glioblastoma-related seizures has not been well characterized. Only one study described an amplification of genes encoding receptor tyrosine kinases (RTK) as a positive predictor for intraoperative seizures during craniotomy. METHODS: 59 patients who underwent surgery with confirmed IDH-wildtype glioblastoma, WHO grade 4, were included. Genome-wide DNA methylation profiling was performed using an 850k Illumina EPIC array and classified by the DKFZ brain tumor classifier. Methylation glioblastoma subclasses and gene alterations were correlated with clinical characteristics including preoperative and long-term seizures. RESULTS: Overall, 18 of 59 patients (30.5%) presented with seizures of whom suffered 8 (44.4%) from a focal and 10 (55.6%) from a generalized seizure. Correlation of preoperative seizures with glioblastoma subclasses and DNA genes identified a higher incidence of preoperative seizures in patients with the glioblastoma subclass of receptor tyrosine kinase II (RTK; EGFR amplified) (p=0.031). In addition, these patients were more likely to present with generalized seizures (p=0.05). In multivariate analysis, temporal location (p=0.014, OR 5.785) but moreover RTK II (p=0.024, OR 7.052) was most predictive for preoperative seizures. Furthermore, recurrent seizures with an increased antiepileptic medication at last follow-up (mean: 9.2 months) occurred more often in RTK II-glioblastoma (p< 0.05). Kaplan-Meier curves showed no significant association between the presentation of seizures and overall or progression-free survival. In addition, further survival analyses did not reveal a correlation of methylation glioblastoma subgroups with the outcome. CONCLUSION: Our study showed a strong correlation of the RTK II methylation subclass with preoperative and long-term seizures in patients suffering from glioblastoma.